Dual image-based reversible fragile watermarking scheme for tamper detection and localization - Sahu, Aditya Kumar; Sahu, Monalisa; Patro, Pramoda; Sahu, Gupteswar; Nayak, Soumya Ranjan (Pattern analysis and applications : PAA, 2023)
This study proposes an efficient dual image-based reversible fragile watermarking scheme (DI-RFWS) that can accurately detect and locate the tampering regions from an image. The proposed scheme embeds two secret bits in each host image (HI) pixel using a pixel readjustment strategy to obtain dual watermarked images (WIs). The pixel readjustment strategy performs a maximum modification of ± 1 to the non-boundary pixels of an image based on the watermark information. The results of the study suggest that in addition to reversibility, the proposed scheme offers triple objective of high capacity, better perceptual transparency, and robustness. Experimental results also show that the proposed scheme achieves a superior peak signal-to-noise ratio (PSNR) of above 52 dB for both the WIs. Further, the proposed scheme can efficiently detect and locate the tampering regions from an image with a high true positive rate, low false positive and negative rate for various tampering rates. Additionally, the proposed scheme shows superior resistance against various intentional and unintentional attacks.